1998
DOI: 10.1590/s0103-84781998000100011
|View full text |Cite
|
Sign up to set email alerts
|

Levomepromazina e atropina como medicações pré-anestésicas na anestesia pela associação tiletamina/zolazepam, em cães

Abstract: O objetivo desta pesquisa foi avaliar o emprego da atropina e da levomepromazina como medicações pré-anestésicas para a anestesia pela associação tiletamina/zolazepam. Foram empregados 30 cães, distribuídos em três grupos iguais. O grupo 1 (controle) foi tratado com 0,2 ml/kg de solução fisiológica (placebo) por via intravenosa; o grupo 2 com 0,044mg/kg de sulfato de atropina por via subcutânea e o grupo 3 com 1mg/kg de cloridrato de levomepromazina por via intravenosa. Quinze minutos após, todos os grupos rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In dogs treated with medetomidine/isoflurane or isoflurane only , there was an accentuated decrease in BIS as compared to dogs treated with isoflurane only, and so, in conformity with the same authors 56,57,59 . In both groups the electromyography was more accentuated from M2 to M4 characterizing the synergism among the a-2 agonist, buprenorphine and midazolam which suppressed the cataleptoid effects of ketamine and the presence of muscular tonus due to ketamine, the same observed by an author 4 , but not observed by others .. 11,46,60 The reported recovery period is variable 10 , around 76 or down to 64 minutes, approximately. The values were lower than those obtained by other authors and showed that the continuous infusion has an advantage for no significant alterations occurred in the physiological parameter, a better quality and decrease the drugs mass dosis to be utilized.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In dogs treated with medetomidine/isoflurane or isoflurane only , there was an accentuated decrease in BIS as compared to dogs treated with isoflurane only, and so, in conformity with the same authors 56,57,59 . In both groups the electromyography was more accentuated from M2 to M4 characterizing the synergism among the a-2 agonist, buprenorphine and midazolam which suppressed the cataleptoid effects of ketamine and the presence of muscular tonus due to ketamine, the same observed by an author 4 , but not observed by others .. 11,46,60 The reported recovery period is variable 10 , around 76 or down to 64 minutes, approximately. The values were lower than those obtained by other authors and showed that the continuous infusion has an advantage for no significant alterations occurred in the physiological parameter, a better quality and decrease the drugs mass dosis to be utilized.…”
Section: Resultsmentioning
confidence: 69%
“…This is a controversial effect for a-2 agonists lead to peripheral vasodilatation and heat production reduction. Different dissociative anesthesia protocols used by some authors 10,11 showed a greater decrease in RT as related to methotrimeprazine effects when used in the combination, as cited before 12 . Both groups showed a decrease in respiratory frequency (f) but still within the physiological limits (10-40 breaths/min) 9 , also observed in dogs treated with atropine/romifidine/ketamine 13. No relevant alterations occurred 14, 15, and 16 in f when the treatment was with a combination of medetomidine to other drugs dogs treated with medetomidine/butopharnol/midazolam showed bradypnea which could be associated to the butopharnol administration 19 and in dogs treated with medetomidine/ butopharnol/ketamine.…”
Section: Resultsmentioning
confidence: 71%